Advances and challenges in CAR-T cell therapy for head and neck squamous cell carcinoma - Sahand Saeidpour Masouleh; Kamyar Nasiri; Ava Ostovar Ravari; Mona Saligheh Rad; Kiarash kiani; Ali Sharifi Sultani; Seyedeh Tabasom Nejati; Mohsen Nabi Afjadi (Biomarker Research)
Abstract Head and neck squamous cell carcinoma (HNSCC) remains among the most aggressive malignancies with limited treatment options, especially in recurrent and metastatic cases. Despite advances in surgery, radiotherapy, chemotherapy, and immune checkpoint inhibitors, survival rates remain suboptimal due to tumor heterogeneity, immune evasion, and treatment resistance. In recent years, Chimeric Antigen Receptor (CAR) T-cell therapy has revolutionized hematologic cancer treatment by genetically modifying T cells to target tumor-specific antigens like CD19, CD70, BCMA, EGFR, and HER2, leading to high remission rates. Its success is attributed to precise antigen recognition, sustained immune response, and long-term immunological memory, though challenges like cytokine release syndrome and antigen loss remain. Notably, its translation to solid tumors, including HNSCC, faces significant challenges, such as tumor microenvironment (TME)-induced immunosuppression, antigen heterogeneity, and limited CAR T-cell infiltration. To address these barriers, several tumor-associated antigens (TAAs), including EGFR, HER2 (ErbB2), B7-H3, CD44v6, CD70, CD98, and MUC1, have been identified as potential CAR T-cell targets in HNSCC. Moreover, innovative approaches, such as dual-targeted CAR T-cells, armored CARs, and CRISPR-engineered modifications, aim to enhance efficacy and overcome resistance. Notably, combination therapies integrating CAR T-cells with immune checkpoint inhibitors (e.g., PD-1/CTLA-4 blockade) and TGF-β-resistant CAR T designs are being explored to improve therapeutic outcomes. This review aimed to elucidate the current landscape of CAR T-cell therapy in HNSCC, by exploring its mechanisms, targeted antigens, challenges, emerging strategies, and future therapeutic potential.